45.1k views
5 votes
Solve the equation, justify
each step with an algebraic
property.
-45 = 5(x + 3)

User Chemikadze
by
4.7k points

1 Answer

4 votes

Answer:

x = -12

Explanation:

Given expression:

-45 = 5(x + 3)

the solution of an algebraic expression is the value(s) that makes the expression true.

In this problem, let us solve for x;

-45 = 5(x + 3)

Applying the distributive property on the right hand side;

-45 = 5x + 15

Now, add (-15) to both sides of the expression;

-45 + (-15) = 5x + 15 + (-15)

-45 - 15 = 5x

-60 = 5x

Then divide both sides by 5;

x = -12

User Ctc Chen
by
4.7k points